Towards an Externalist History of Islamic Science (American Journal of Islam and Society, 1992)
This essay will attempt to propose a methodology for the study of the historyof Islamic science. The method outlined below offers a way of reinterpretingthe history of Islamic science and covers those angles that have been obscuredby the method of narrative writing. The project itself remains an immense oneand cannot be simply dismissed, as there is always room for reinterpretation.Foucault writes: “History shows that everything that has been thought of willbe thought of again by a thought that does not yet existl’l There is no value inthe glorification of the past if that glorification hides the conflict within thetradition-a conflict that may remain unresolved.The central focus of this study will be that of the externalist method ratherthan the intemalist method. To the internalist, the methodology of science followsa rational course: to theexternalist, many irrational factors, at times beyond therational, may influence the direction of science. However, one must state, withcaution, that both methods are indispensable, for the development of sciencecan only be understood with a clear insight into how they intersect in the evolutionof science as a body of knowledge. Besides presenting an evolution of scientificideas, they give an insight into scientific research itself and, secondly, into thesociological context in which science developed. This is only possible, Kuhnstates, if there is a bridge between internal history (which concerns itself withthe evolution of the field, its chief actors, and in what way their discoveries andmethods have helped to develop the field [this view is insular as it argues that ...